Rekonstruksi Kuliner Lokal untuk Memperkuat Branding Makanan Tradisional Labuan Bajo - Suprastayasa, I Gusti Ngurah Agung; Rumadana, I Made; Sabudi, I Nyoman Sukana; Kalpikawati, Ida Ayu; Wiryanata, I Gusti Ngurah Agung; Febrianto, I Gusti Agung; Pinaria, Ni Wayan Chintia (JURNAL GASTRONOMI INDONESIA, 2024)
As a super priority and newly developing destination, the Labuan Bajo tourism area can use traditional culinary delights to attract tourist visits. However, only a few conventional culinary delights are marketed to domestic and foreign tourists. The existence of traditional culinary delights has proven to be a tourist attraction. Therefore, this research aims to identify traditional Labuan Bajo cuisine and reconstruct these culinary delights for tourists. This research is qualitative research using informants determined using purposive sampling techniques. Interviews, documentation studies, and observations carried out data collection. The data analysis techniques used in this research are data reduction, data presentation, and conclusion. The research results show that the types of traditional Labuan Bajo culinary delights that are still maintained include Corn Bose, Roti Kompyang, Rebok, Lomak, Nasi Kolo, Tibu, Fish in Sour Sauce, Rumpu Rampe. Several traditional Labuan Bajo culinary delights that can be reconstructed are arranged in a table d'hote menu based on aroma, texture/shape consistency, nutrition, culinary appearance, smell, and temperature. Example of a menu that is recommended for reconstruction to be displayed in the table d'hote menu, including Appetizer: Fried Salted Cara Fish and Beef Sei with Papaya Flower, Soup: Fish in Sour Sauce Soup and Ndusuk Leaf Vegetables, Main Course: Pork /Chicken Tibu, Grilled/Fried Fish with Onion Sauce, Nasi Kolo/Corn Bose/Hangbesar, Lomak/Rumpu Rampe, Dessert: Rebok Praline With Grilled Banana and Cassava, and Bread: Roti Kompyang.